Total plate count dalam isi telur ayam ras di pasar tradisional Kecamatan Waru, Kabupaten Sidoarjo - Kirana, Sabila Citra; Lestari, Tita Damayanti; Budiarto; Puspitasari, Yulianna; Mutamsari Witaningrum, Adiana; Permatasari, Dian Ayu; Budiarto, Budiarto (School of Veterinary Medicine and Biomedical Sciences, IPB University, Bogor, Indonesia, 2023)
Background: Microbial contamination in consumed chicken eggs can endanger human health. Bacteria can grow and develop in food so that it can reduce the food quality. Determination of food quality can be done by various methods, one of which is Total Plate Count (TPC). Objective: The aim of this study was to determine the level of bacterial contamination in chicken eggs sold at traditional markets in Waru District, Sidoarjo Regency. Methods: Thirty samples were collected from two traditional markets, Waru Market and Wadung Asri Market. This study used the pour plate method of TPC test. Egg contents were diluted and then inoculated in Nutrient Agar. The media inoculated with the sample suspension was incubated at 37°C for 24 hours. The growing bacterial colonies were counted and analyzed using the Standard Plate Count. This study's data are presented descriptively and compared with the Indonesian National Standard (SNI) 7388-2009 maximum requirement of contaminant bacteria in chicken eggs is 1×105 CFU/mL. Results: The results showed that the averages TPC in two traditional markets were 2.1×104 CFU/mL in Waru Market and 3.4×103 CFU/mL in Wadung Asri Market. The average TPC still meets the maximum limit of microbial contamination listed in SNI 7388-2009. Conclusion: The average values of TPC in both markets are not the same, but the qualities of chicken eggs sold in Waru Market and Wadung Asri Market are good and suitable for consumption.